The Beef Between Men and Animals: Meat-Eating and Masculinity in the U.S. - A Case Study of Objectifying Fast-Food Advertising in the Anglosphere - Klainberger, Sarah Agnes Thonsgaard (Leviathan: Interdisciplinary Journal in English, 2020)
Fast-food companies often rely on images objectifying women in their advertising as a way to sell their products. Following Carol J. Adams’ work on absent referents, this article argues that they rely on ideas and images objectifying animals as well. However, the use of these ideas and images is problematic because the normalization of the objectification of non-human animals and women in fast-food advertising can have consequences for both as it perpetuates animal exploitation and gender inequality. This article analyzes three examples of fast-food advertising from Arby’s, Carl’s Jr., and Burger King which arguably contribute to the normalization of the objectification of animals and women through their perpetuation of the problematic notion that eating animals is both natural and masculine. The analysis illustrates links between women and non-human animals in advertising and supports the linked oppression theory.